HUBUNGAN PENGELOLAAN KELAS DENGAN MOTIVASI BELAJAR SISWA KELAS V DI SD NEGERI 137 PALEMBANG - Tuti Susilowati; Erma Yulaini; Robert Budi Laksana (Jurnal Tunas Pendidikan, 2026)
The problem in this study is whether there is a relationship between classroom management and student learning motivation at SD Negeri 137 Palembang. The purpose of this study was to determine the relationship between classroom management and student learning motivation at SD Negeri 137 Palembang. This research method uses descriptive quantitative. Data collection techniques are questionnaires and documentation. The data analysis technique used is the product moment correlation hypothesis test. Based on the questionnaire results, it can be seen that the average student questionnaire results are 76.3 and 75.7. Based on the results of the calculation of the overall correlation of variable X with variable Y, the rcount value is 0.701 with a good level of relationship, while the rtable value with a significant level of 0.05 and n = 24 obtained an rtable value of 0.404. It is known that the value of rcount ≥ rtable, so it can be stated that the hypothesis is accepted. Based on the coefficient of determination, the level of relationship between variable (x) and variable (y) is 50.86%.